PENGARUH PERSEPSI MAHASISWA ATAS BAHASA INDONESIA DAN MINAT BELAJAR TERHADAP PRESTASI BELAJAR BAHASA INDONESIA - Hilda Hilaliyah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2015)
Abstract: The goal of this study was to find out and analyse the effect of students’ perception on Indonesian language and learning interest towards their learning achievement about Indonesian language subject. A survey was conducted on students of Art and Design School at one of private local universities in South Jakarta. The survey utilized a questionnaire and classroom score record with 60 student participants using random sampling method. The result was then analysed by employing regression and correlation analysis techniques. The data indicates: (1) there is a significant effect on students’ perception of Indonesian language and learning interest towards learning achievement, (2) there is also a significant effect on the students’ perception of Indonesian language towards their learning achievement on this particular subject, and (3) result shows a significant effect on learning interest towards learning achievement on Indonesian language subject. Keyword: students’ perception, Indonesian language, learning interest, learning